2010
DOI: 10.3171/2009.10.focus09207
|View full text |Cite
|
Sign up to set email alerts
|

The many roles of microRNAs in brain tumor biology

Abstract: MicroRNAs (miRNAs) are now recognized as the primary RNAs involved in the purposeful silencing of the cell's own message. In addition to the established role of miRNAs as developmental regulators of normal cellular function, they have recently been shown to be important players in pathological states such as cancer. The authors review the literature on the role of miRNAs in the formation and propagation of gliomas and medulloblastomas, highlighting the potential of these molecules and their inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 76 publications
0
39
0
1
Order By: Relevance
“…Previous studies have demonstrated that single nucleotide polymorphisms (SNP) or mutations in miRNA sequences may affect cancer susceptibility by altering miRNA expression, maturation or miRNA-mRNA interaction (9,10). Aberrant miRNA expression has been consistently reported to be associated with oncogenesis (11,12) and the deregulated expression of miRNAs and their targets may result from functional polymorphisms in the miRNA sequence (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that single nucleotide polymorphisms (SNP) or mutations in miRNA sequences may affect cancer susceptibility by altering miRNA expression, maturation or miRNA-mRNA interaction (9,10). Aberrant miRNA expression has been consistently reported to be associated with oncogenesis (11,12) and the deregulated expression of miRNAs and their targets may result from functional polymorphisms in the miRNA sequence (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Discovery of the posttranscriptional modulation of gene expression via small RNAs has led to a huge number of publications in areas such as cancer and brain development (Fineberg et al 2009;Turner et al 2010) Expression levels on day 4 were significantly less than at any other day (a, b Bonferroni test; p \ 0.05). The DC t levels were subtracted from 10 so that higher values reflect higher expression.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, medulloblastoma (MB) is the most common brain malignancy in children that arises from altered development of cerebellar progenitor cells [69]. MicroRNAs certainly play critical roles in cancer initiation, progression, and some of them could be considered as clinical biomarkers for cancer diagnosis, prognosis and prediction of therapeutic response [70]. Specifically, expression profiling studies have revealed extensive alteration of microRNAs in primary glioblastoma, suggesting that microRNAs may represent a new class of genes involved in …”
Section: Micrornas In Brain Tumor Developmentmentioning
confidence: 99%